Periodontal health of the geriatric population in old-age homes of Delhi, India - Nisha Rani Yadav; Meena Jain; Ankur Sharma; Vishal Jain; Shilpi Singh; Arundeep Singh; Vamsi Krishna Reddy; Shourya Tandon (Wolters Kluwer Medknow Publications, 2021)
Background: Periodontal disease is one of the leading causes of tooth loss in the geriatric population. Assessment of periodontal disease in a population is an important step in planning effective prevention and control programs for periodontal disease. Therefore, a study was carried out in old-age homes of Delhi to assess the periodontal status of 65-74-year-old elderly and recommend interventions to improve their periodontal health. Materials and Methods: A cross-sectional study was conducted among 464 elderly from old-age homes of Delhi. Periodontal health status of the participants was determined using the WHO oral health assessment form. Community Periodontal Index (CPI) and loss of attachment (LOA) were recorded. Collected data were analyzed using SPSS version 23. Chi-square test was used to determine statistically significant difference among CPI scores and LOA according to age and gender. P ≤ 0.05 was considered statistically significant. Results: The result of the study showed that 25.4% of the elderly had healthy periodontium, 71.1% had a periodontal pocket of 6 mm or more, and 2.40% had a pocket depth of 4-5 mm. Around 36% had 6-8 mm LOA and 34.70% had 9-11 mm LOA. The difference between CPI scores among gender and age group was not significant (P = 0.20, P = 0.096). However, the difference among gender for LOA was found significant (P = 0.014). Conclusion: The results from this study show that periodontal health of elderly residing in old-age homes is very poor. The periodontal status of this population can be enhanced by special collaborative efforts from the government and various nongovernmental organizations toward preventive and curative periodontal health services.